2022
DOI: 10.1136/jitc-2021-004043
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomal CD73 from serum of patients with melanoma suppresses lymphocyte functions and is associated with therapy resistance to anti-PD-1 agents

Abstract: BackgroundCD73 is an ectonucleotidase producing the immunosuppressor mediator adenosine. Elevated levels of circulating CD73 in patients with cancer have been associated with disease progression and poor response to immunotherapy. Immunosuppressive pathways associated with exosomes can affect T-cell function and the therapeutic efficacy of anti-programmed cell-death protein 1 (anti-PD-1) therapy. Here, we conducted a retrospective pilot study to evaluate levels of exosomal CD73 before and early during treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 52 publications
(61 reference statements)
0
30
0
Order By: Relevance
“…Frontiers in Cell and Developmental Biology frontiersin.org melanoma, CD73 is expressed also on exosomes from serum of patients and contributes to lymphocyte T functions suppression and influences the response to anti-PD1 therapy (Turiello et al, 2022). Blocking of both CD73 and A2AR adenosine signaling at the same time, reduces tumor growth and metastasis and improves antitumor immune responses (Young et al, 2016).…”
Section: Purinergic Signaling and Immunotherapy Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Frontiers in Cell and Developmental Biology frontiersin.org melanoma, CD73 is expressed also on exosomes from serum of patients and contributes to lymphocyte T functions suppression and influences the response to anti-PD1 therapy (Turiello et al, 2022). Blocking of both CD73 and A2AR adenosine signaling at the same time, reduces tumor growth and metastasis and improves antitumor immune responses (Young et al, 2016).…”
Section: Purinergic Signaling and Immunotherapy Resistancementioning
confidence: 99%
“…The deficiency of CD73 in CD8 + T cells leads to an increase of IFN-γ, TNFα, granzime B production and mitochondrial respiration, meaning that this ectonucleotidase restraints CD8 + T cells metabolic fitness ( Briceño et al, 2021 ) ( Figure 2B ). In melanoma, CD73 is expressed also on exosomes from serum of patients and contributes to lymphocyte T functions suppression and influences the response to anti-PD1 therapy ( Turiello et al, 2022 ). Blocking of both CD73 and A2AR adenosine signaling at the same time, reduces tumor growth and metastasis and improves antitumor immune responses ( Young et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 ]. PD-L1 is present in exosomes released from melanoma cells [ 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 ]; however, exosomes derived from metastasised melanoma cells have a higher PD-L1 content than those derived from primary focal melanoma cells. Moreover, an electron microscope analysis revealed the PD-L1 protein was carried on the surface of the protein [ 187 ].…”
Section: Ev-mediated Immune Escape Of Cancer Cellsmentioning
confidence: 99%
“…By transporting nucleic acids, proteins, lipids, amino acids, and metabolites, EVs play an important role in facilitating remote signal transmission in an organism, which is vital to the multi-organ collaboration and maintenance of normal physiological functions [4,5]. Many physiological processes have been discovered to be related to the EVs [6][7][8][9]. For example, Grizzle et al found that tumor-derived vesicles could bear immunosuppressive molecules, inactivating T lymphocytes or natural killer cells or promoting the differentiation of regulatory T lymphocytes or myeloid cells to suppress immune responses [10].…”
Section: Introductionmentioning
confidence: 99%